Customer satisfaction on e-SERVQUAL in Islamic online banking services / Nurhazirah Hashim …[et al.] - Hashim, Nurhazirah; Mohd Salleh, Mohammad Zaim; Muhamad Yunus, Nor Sara Nadia; Mat Shafie, Intan Syafinaz (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia, 2017)
The recent development in the ecommerce services has shown a variety of established companies participating in the web business environment including Islamic banks. Business with the most experience and success in using ecommerce are beginning to realize that the indicator of success or failure of the ecommerce environment was included in the online services. Nowadays, the trend of a business is to serve the customer with best quality of services to enhance the consumer satisfaction and compete with the global competitors as online services enabled registered user to make products purchase transaction only through website such as check and manage financial standing, transfer funds, bill payment, prepaid reload and so forth. However, in recent times, Islamic banking users faced problems with the online system such as cannot log in to the system, payment failure and mostly security and privacy hindrance. Therefore, this study aimed to investigate the relationship between electronic service quality (e-SERVQUAL) and customer satisfaction towards Islamic Online Banking Services users. Based on the sample size, only 76 respondents were selected to participate in this study by using a convenience sampling. Further, Pearson correlation and multiple regression were reported to analyze the mentioned relationship. The findings have shown that there is a positive relationship between e-SERVQUAL and customer satisfaction in using Islamic online banking services. Based on the findings, Islamic online banking developer is recommended to improve more on their responsiveness in order to provide quick response to their customer’s requirements. Moreover, they also should be more reliable in providing accurate information in performing the promised services. They must assure that all of their customers can quickly get responds and true feedback regarding their problems to ensure customer satisfy with service provided. Besides, the safety of the website and the protection of customer information also considered a vital action that should be concerned in order to increase the customers’ satisfaction.